IMPLEMENTASI BUDAYA KERJA DALAM MENINGKATKAN KEDISIPLINAN GURU DI MADRASAH ALIYAH PROYEK UNIVA MEDAN TAHUN AJARAN 2019-2020IMPLEMENTASI BUDAYA KERJA DALAM MENINGKATKAN KEDISIPLINAN GURU DI MADRASAH ALIYAH PROYEK UNIVA MEDAN TAHUN AJARAN 2019-2020 - Amir, Khairul (Fakultas Agama Islam, 2020)
This Study Aims To Determine The Implementation Of Work Culture In Improving Teacher Discipline In Madrasah Aliyah Medan UNIVA Project. To get this data, the population is all 33 teachers. The sample was determined using 33 random sampling techniques. The metthod in this research is descriptive method with data collection instruments is a questionnaire of 5 items. Based on data analysis and management techniques, the following research results are obtained: The Implementation Of Work Culture In Improving Teacher Discipline In Madrasah Aliyah Medan UNIVA Project school year 2019/2020 in this case equal 85,56% from 33 the teacher states that the discipline of islamic/general religious education teachers positively implements discipline in Madrasah Aliyah UNIVA Medan Project This Study Aims To Determine The Implementation Of Work Culture In Improving Teacher Discipline In Madrasah Aliyah Medan UNIVA Project. To get this data, the population is all 33 teachers. The sample was determined using 33 random sampling techniques. The metthod in this research is descriptive method with data collection instruments is a questionnaire of 5 items. Based on data analysis and management techniques, the following research results are obtained: The Implementation Of Work Culture In Improving Teacher Discipline In Madrasah Aliyah Medan UNIVA Project school year 2019/2020 in this case equal 85,56% from 33 the teacher states that the discipline of islamic/general religious education teachers positively implements discipline in Madrasah Aliyah UNIVA Medan Project.